Bictegravir versus dolutegravir, each with emtricitabine and tenofovir alafenamide, for initial treatment of HIV-1 infection: a randomised, double-blind, phase 2 trial. Issue 4 (April 2017) - Sax, Paul E; DeJesus, Edwin; Crofoot, Gordon; Ward, Douglas; Benson, Paul; Dretler, Robin; Mills, Anthony; Brinson, Cynthia; Peloquin, Julie; Wei, Xuelian; White, Kirsten; Cheng, Andrew; et al.
Summary: Background: All recent treatment guidelines recommend integrase strand transfer inhibitors (INSTIs) as components of initial HIV therapy. Bictegravir, a novel, once-daily, unboosted INSTI, showed potent activity in a 10 day monotherapy study and has a high in-vitro resistance barrier. On the basis of these results, we did a phase 2 trial comparing bictegravir with dolutegravir. Methods: In this randomised, double-blind, phase 2 trial, we recruited previously untreated adults (aged ≥18 years) with HIV-1 infections from 22 outpatient centres in the USA. Eligible patients had HIV-1 RNA concentrations of at least 1000 copies per mL, CD4 counts of at least 200 cells per μL, estimated glomerular filtration rates of at least 70 mL per min, and HIV-1 genotypes showing sensitivity to emtricitabine and tenofovir. We excluded patients if they were hepatitis B-co-infected or hepatitis C-co-infected, had new AIDS-defining conditions within 30 days of screening, or were pregnant. We randomly allocated participants (2:1) to receive oral once-daily 75 mg bictegravir or 50 mg dolutegravir with matching placebo plus the fixed-dose combination of 200 mg emtricitabine and 25 mg tenofovir alafenamide for 48 weeks. We randomly allocated participants via an interactive web system, stratified by HIV-1 RNA concentration. Investigators, patients, study staff giving treatment, collecting data, and assessing outcomes, and the funder were masked to treatment group. The primary outcome was the proportion of participants with plasma HIV-1 RNA concentrations of less than 50 copies per mL at week 24 according to the US Food and Drug Administration-defined snapshot algorithm. We included all participants receiving one dose of study drug in analyses. This trial is registered withClinicalTrials.gov, numberNCT02397694 . Findings: Between March 23, 2015, and May 21, 2015, we screened 125 patients, randomly allocating and giving study drug to 98 (65 received bictegravir plus emtricitabine and tenofovir alafenamide and 33 received dolutegravir plus emtricitabine and tenofovir alafenamide). At week 24, 63 (96·9%) of 65 in the bictegravir group had HIV-1 RNA loads of less than 50 copies per mL compared with 31 (93·9%) of 33 in the dolutegravir group (weighted difference 2·9%, 95% CI −8·5 to 14·2; p=0·50). Treatment-emergent adverse events were reported by 55 (85%) of 65 participants in the bictegravir plus emtricitabine and tenofovir alafenamide group versus 22 (67%) of 33 in the dolutegravir plus emtricitabine and tenofovir alafenamide group. The most common adverse events were diarrhoea (eight [12%] of 65 vs four [12%] of 33) and nausea (five [8%] of 65 vs four [12%] of 33). One participant taking bictegravir plus emtricitabine and tenofovir alafenamide discontinued because of a drug-related adverse event (urticaria) after week 24. No treatment-related serious adverse events or deaths occurred. Interpretation: Bictegravir plus emtricitabine and tenofovir alafenamide and dolutegravir plus emtricitabine and tenofovir alafenamide both showed high efficacy up to 24 weeks. Both treatments were well tolerated. Administration of bictegravir, a novel, potent, once-daily INSTI designed to improve on existing INSTI options with the backbone of emtricitabine and tenofovir alafenamide, might provide an advantage to patients. Funding: Gilead Sciences.